Identifikasi Kata Serapan Dala Buku Paket Kurikulum 2013 Bahasa Indonesia Wahana Pengetahuan Smp Kelas Vii - Ayu Probo Lestari, Diah; , Prof. Dr. Markamah, M.Hum; , Laili Etika Rahmawati, S.Pd., M.Pd (2016)
Issues raised in this research is the analysis of Linguistics kususnya Uptake word contained in Package Books Curriculum 2013 Indonesian Forum for Knowledge Junior Class VII. This study aims to (1) Describe the form of a loan word contained in textbooks curriculum 2013 Indonesian Forum for Knowledge Junior Class VII. (2) Describe the student's understanding of the words used in textbooks serapanyang curriculum 2013 Indonesian Forum for Knowledge VII.Penelitian junior class uses methods and techniques refer to the note, the note or take a picture of research data and then to take the objects to be studied. Methods and techniques of data analysis using a unified method intralingual and match ekstralingual with BUL techniques. Loan word contained in the texts in textbooks Curriculum 2013 Indonesian Forum for Knowledge Junior Class VII consists of two. The first use of the word uptake by adjusting the spelling and pronunciation. The second use of the word uptake without adjustment spelling and pronunciation. The use of the word uptake by adjusting the spelling and pronunciation of words that comprise 66 is divided into two, namely the absorption of foreign terms into Indonesian by adjusting suffixes and prefixes. A. Adjustment suffixes include (1) - (a) the absorbed of - (a) tion (English), (2) -i absorbed from -y (England), Bags absorbed from -ty (English), (4) -ik absorbed from -ic, ique (English), (5) -logi absorbed from logy (English), (6) -is absorbed from -ic, -ical (English), (7) -or absorbed from (English) -or, (8) -iL absorbed from -ile, -le (England). B. Adjustment prefixes include (1) Co, com-, con absorbed from co, compass, con-, (2) analogous, an- absorbed from analogous, anionic, (3) Trans- absorbed from trans -, (4) eco- nomic absorbed from, (5) re- re- absorbed from as much as 1 data (6) im-, in-, il- absorbed from im-, in-, il-, (7) ex- absorbed from expression, (8) ad-, ac- absorbed from ad-, AK. Said uptake by the use of words without adjustment uptake spelling and pronunciation includes a loan word relevant, biota, ritual, protein, festivals, popular, internet. After testing questions about a loan word to the students of SMP SMP Negeri 1 Tanon found 15 loan word that is not understood by the students